METHODS AND TECHNIQUES OF SOCIAL REHABILITATION OF COMBAT VETERANS - Nataliya L. Klyachkina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The chosen research topic is relevant, especially in recent times when the Russian and the whole international community is talking about the new "hot spots", that inevitably increase the number of people affected during or as a result of the fighting. More horrific consequences of these events can be seen in the usual "peaceful" life of former participants of military clashes and conflicts. Therefore, all the more relevant is the subject of psychological assistance to former combatants for their reintegration and rehabilitation into everyday life. Rehabilitation can have a temporary, but significant success, leading to a sharp improvement of the quality of life. The peculiarities of the personality of combat veterans and maladaptive manifestations of their behavior and their causes should be considered in the organization of their rehabilitation.